Professionalization and socioemotional wealth in family businesses. Bogota case - Espitia, Yurani López; Grisales-Aguirre, Andres; Gutierrez, Jorge Gamez (International Journal of Innovative Research and Scientific Studies, 2025)
This research investigates the ways in which professionalization and socio-emotional wealth (SEW) collectively influence the performance of small and medium-sized enterprises (SMEs) owned by families. An analysis was conducted on a cross-sectional survey involving 205 family businesses located in Bogotá, utilizing confirmatory factor analysis and structural equation modeling. The validated model features four dimensions, including business objectives, management practices, organizational, and individual requirements. Structured management approaches, which we use as a measure of professional development, have a significant positive impact on the success of organizations , although clearly defined strategic goal setting demonstrates a minor but important impact . The individual requirements of family heads can adversely affect achievement (β = -0.471), but also initiate management strategies, creating a beneficial indirect outcome that balances things out . The model accounts for 34 percent of the variation in success . The concepts of professionalization and socioemotional wealth are not in opposition; when management practices honor family identity, both technical effectiveness and emotional objectives work together as valuable competitive assets. Owners of family businesses and their advisors ought to create professionalization initiatives that (i) establish strategic planning and management based on evidence and (ii) openly recognize the aspirations of leaders for acknowledgment, authority, and the preservation of their legacy. The diagnostic framework can be adapted for different areas and industries, and future research should explore moderating factors such as the generational level or market instability to improve guidelines that boost efficiency while maintaining family identity.